2018
DOI: 10.1016/j.clinthera.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Sequencing in Patients With Inflammatory Bowel Disease

Abstract: While current treatment options seem effective in a proportion of patients with UC and CD, others require multiple lines of therapy, suggesting anunmet need for alternative treatments in UC and CD to achieve disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The effectiveness and tolerability of biologic therapy was indicated by the persistence findings, which account for both treatment switches and discontinuations. In our analysis, over half of patients discontinued biologic treatment during their clinical course, and mean time to loss of biologic persistence was > 12 months, which is comparable to that reported in previous studies [12,18,[26][27][28][29]. The relatively low rate of intestinal complications (33%) and surgery (22%) following biologic introduction, and long mean time between first biologic introduction and first complication (of about 10 months) or first surgery (of just under 2 years) suggests a role of biologics in preventing CD complications and delaying the need for surgical intervention, as seen in other observational studies and clinical trials [30-32].…”
Section: Discussionsupporting
confidence: 88%
“…The effectiveness and tolerability of biologic therapy was indicated by the persistence findings, which account for both treatment switches and discontinuations. In our analysis, over half of patients discontinued biologic treatment during their clinical course, and mean time to loss of biologic persistence was > 12 months, which is comparable to that reported in previous studies [12,18,[26][27][28][29]. The relatively low rate of intestinal complications (33%) and surgery (22%) following biologic introduction, and long mean time between first biologic introduction and first complication (of about 10 months) or first surgery (of just under 2 years) suggests a role of biologics in preventing CD complications and delaying the need for surgical intervention, as seen in other observational studies and clinical trials [30-32].…”
Section: Discussionsupporting
confidence: 88%
“…The American College of Gastroenterology (ACG) recommends treatment with biologic agents such as adalimumab (ADA), certolizumab pegol (CZP), infliximab (IFX), and vedolizumab (VDZ) for patients who fail to respond, lose response, or are intolerant to conventional treatment [1,10,11]. These treatments are prescribed to attain and maintain clinical remission, slow disease progression, and delay surgical interventions [12]. However, between one-third and one-half of patients do not respond to anti-tumor necrosis factor (anti-TNF) treatments, which necessitates the introduction of a second biologic.…”
Section: Introductionmentioning
confidence: 99%
“…Switching to other medications ranges from 11% to 35% [20]. Brady et al [12] noted that only one-third of CD patients remained on a biologic treatment over a 12-month follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 54.0% of patients with UC newly initiated on a biologic (adalimumab, certolizumab, golimumab, infliximab, natalizumab, ustekinumab or vedolizumab) were reported to remain on their first-line therapy at 1 year based on another analysis of the same US insurance claims database. 15 However, McDermott et al reported only 35.0% (n=8/23) of patients receiving adalimumab persisting at 1 year. 14 This Irish study might be linked to the low patient numbers, as only 23 out of 3000 patients were found to be patients with UC receiving adalimumab with a high percentage of previous biologic failure (20 of 23 patients had previously received infliximab).…”
Section: Discussionmentioning
confidence: 98%
“…Published studies report treatment persistence rates at 1 year for biologics ranging from 35.0% to 63.0% in patients with UC from Ireland, the USA and Canada. [13][14][15][16][17] A number of observational studies have explored treatment response in the three antitumour necrosis factor (anti-TNF) agents currently licensed for use in UC. These have included multicentre cohort studies of adalimumab and golimumab in Spain, 18 19 an observational study of golimumab in Italian primary IBD centres 20 and a retrospective analysis of the outcomes of infliximab treatment at a Japanese academic hospital.…”
Section: Introductionmentioning
confidence: 99%